2018
DOI: 10.1111/josh.12706
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Physical Activity for Latino and White Middle School‐Aged Children

Abstract: BACKGROUND Physical activity (PA) has long been acknowledged to contribute health benefits among children. However, research has consistently shown that PA declines as children grow older. Thus, this study examined the factors which are associated to children's PA in order to identify potential barriers to PA. METHODS Using data from the KidQuest Program, we conducted bivariate and multivariate analyses on survey data collected from fifth to seventh grade students in a small Midwestern city. RESULTS We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(94 reference statements)
1
1
0
1
Order By: Relevance
“…Additionally, some mothers reported that their children were deterred from being physically active due to distractions by technology (watching television or playing video games). This is consistent with the literature that reported technology as a barrier to physical activity [42][43][44].…”
Section: Arab Mothers' Barriers and Practices Related To Physical Activity Behaviorssupporting
confidence: 93%
“…Additionally, some mothers reported that their children were deterred from being physically active due to distractions by technology (watching television or playing video games). This is consistent with the literature that reported technology as a barrier to physical activity [42][43][44].…”
Section: Arab Mothers' Barriers and Practices Related To Physical Activity Behaviorssupporting
confidence: 93%
“…However, results from the first wave are available and represent sociodemographic variability from Wave 2 (i.e., predominantly White rural communities) ( 34 ). Additionally, we did not account for cultural heterogeneity among Hispanic and racially diverse children and acknowledge the need to examine one’s country of origin, the amount of time in the U.S., and preferred language, explicitly as limiting materials (i.e., PA surveillance instrument and consent forms) to English and Spanish may have resulted in sampling and response biases ( 102 ). Next, there are limitations to the self-report measure of organized YS involvement and PA used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos têm demonstrado uma associação direta entre atividades físicas vigorosas e diminuição do tempo de ecrã, tendo como inferência direta a melhoria da saúde física (HIDALGO-RASMUSSEN; RAMÍREZ-LÓPEZ;MARTÍN, 2013;MOTAMED-GORJI et al, 2019;PIOLA et al, 2019). No entanto, outras publicações indicaram que o tempo de ecrã não é associado diretamente a saúde física(GARCIA et al, 2019;SILVA et al, 2016), ou ainda, consoante o sexo dos jovens existe associação entre saúde física e tempo de ecrã(WINTHER et al, 2015). Outra abordagem é vista em um estudo iraniano de âmbito nacional sobre estudantes do ensino básico e secundário, sugerindo que o aumento da atividade física é mais crucial do que enfatizar a redução do tempo de ecrã para a melhoria do bem-estar(MATIN et al, 2017).Outros fatores também foram estudados em relação à saúde física.…”
unclassified